Kepuasan Dan Loyalitas Pelanggan Logistik Internasional Di Indonesia: Peran Timeliness Dan Information Quality - Yeronica, Fernanda; Laulita, Nasar Buntu (Jurnal Manajerial, 2024)
Background – Globalization and technology advancements have driven the growth of electronic commerce (e-commerce) globally. E-commerce allows business to reach consumers worldwide. In this case, e-commerce relies on quality logistics services, particularly in terms of timeliness and quality of information. Aim – This study aims to assess the influence of timeliness and information quality on customer satisfaction and loyalty, while also examining the mediating role of customer satisfaction on customer loyalty among international logistics service providers in Indonesia. Design/ Methodology/ Approach – This research adopts a quantitative method by collecting primary data through online distribution of questionnaires. The sample consisted of 277 respondents selected through convenience sampling. Data analysis was conducted using the PLS-SEM approach with the SmartPLS3 software. Findings – This research shows that timeliness has a positive and significant impact on customer satisfaction and loyalty. Meanwhile, information quality also has a positive and significant effect on customer satisfaction, although it doesn’t significantly influence customer loyalty. However, customer satisfaction is effective in mediating the relationship between timeliness and information quality with customer loyalty. Conclusion – Timeliness and optimal quality of information in international logistics services in Indonesia can increase customer satisfaction. Moreover, information quality has the potential to build customer loyalty towards the selected logistics service provider. It should be emphasized that customer satisfaction with the timeliness and quality of information provided by logistics service providers is the key to increasing customer loyalty. Research Implication – International logistics service providers in Indonesia must focus on improving timeliness and information quality. By focusing on these areas, international logistics service providers in Indonesia can better serve their customers, increase satisfaction, and ultimately build a loyal customer base. Limitations – This research only focuses on two dimensions of logistics service quality, namely timeliness and information quality.